Heat Transfer Enhancement In Ducts Due To Acoustic Excitation - Bennett, Gareth; Murray, Darina; Persoons, Tim (My University, 2009)
The thermoacoustic effect that results from the interaction of a sound wave in a compressible fluid in contact with solid boundaries is known to be capable of removing heat from power dissipating systems. In this paper the standing wave acoustic field that is generated in an open ended duct, a section of which is heated, and how it interacts with the aerodynamic flow field is examined by an experimental study. Specifically, the effect the fluctuating acoustic pressure and associated particle velocity have on the internal fluid dynamics is investigated. The ultimate goal is to fully understand and optimize the interaction mechanisms in order to enhance the overall convective heat transfer from a heated duct to internal flow. An experimental rig which has been designed and built allows the fundamental fluid dynamic, acoustic and heat transfer mechanisms to be studied. The rig consists of a circular duct with a central copper isothermally heated section which is instrumented with thermocouples, a heat flux sensor, microphones and a cross-wire probe. The cross wire is used to measure both time varying temperature and velocity at a high frequency and spatial resolution and a calibration procedure which allows the sensor to measure fluctuating velocity at elevated temperatures is reported. Results from the current investigation demonstrate how convective heat transfer from the heated duct section to the internal flow is enhanced due to acoustic excitation. In this preliminary, investigative study, it is suggested that two different heat transfer mechanisms are identified: one associated with the increased turbulent mixing due to the added particle velocity; the second associated with acoustic streaming. The results show significant increases in flow temperature and heat transfer coefficients for free and forced convection regimes.
7th World Conference on Experimental Heat Transfer, Fluid Mechanics and Thermodynamics (ExHFT-7)
PUBLISHED
Krak?w, Poland
Keywords: Convective Heat Transfer, Duct Acoustics, Standing Wave; Smart & Sustainable Planet